1990
DOI: 10.1007/bf01536913
|View full text |Cite
|
Sign up to set email alerts
|

Focal ultrasound lesions in liver cirrhosis diagnosed as regenerating nodules by fine-needle biopsy

Abstract: In the period 1985-1988, 62 focal liver lesions in 58 cirrhotic patients were studied by ultrasonography; 12 of these focal lesions were documented to be regenerating lesions by echo-guided fine-needle biopsy. During an average follow-up period of 10.2 months (range 3-22 months), hepatocellular carcinoma was subsequently found in 10 of the cases of regenerating nodules, whereas the initial diagnosis of regenerating nodule was confirmed in the remaining two cases. Based upon this finding, it is suggested that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Indeed the evolution of 10 AHNs into HCC was demonstrated in a study on 12 nodules during a period of observation in the range of 3-22 months, with a mean of 10.2 months [8]. However, in another study [7] in a series of 17 AHNs, no case of malignant transformation was observed after a long follow-up period (13-51 months).…”
Section: Prospective Studymentioning
confidence: 93%
See 2 more Smart Citations
“…Indeed the evolution of 10 AHNs into HCC was demonstrated in a study on 12 nodules during a period of observation in the range of 3-22 months, with a mean of 10.2 months [8]. However, in another study [7] in a series of 17 AHNs, no case of malignant transformation was observed after a long follow-up period (13-51 months).…”
Section: Prospective Studymentioning
confidence: 93%
“…Different selection criteria may explain such findings: in the first series [8], as well as in our retrospective study, all focal lesions without a clear-cut pathological diagnosis of malignancy were taken into account, whereas in the second series [7], nodules showing variable atypical changes were classified as "borderline lesions" and consequently excluded from the study.…”
Section: Prospective Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of focal liver lesions in patients with cirrhosis, the possibility of a diagnosis of hepatocellular carcinoma should be considered, especially in patients who undergo screening by ultrasound and serum α-fetoprotein determination every 6 months. 2,12 Recently the European Association for the Study of the Liver 13 (EASL) suggested that for cirrhotic patients with a focal liver lesion > 2 cm in diameter compatible with hepatocellular carcinoma and identified by at least two imaging techniques it would not be necessary to perform cytological and/or histologic confirmation, with the imaging methods sufficient for the diagnosis of hepatocellular carcinoma. EASL 13 also suggested that punctures be limited to only patients with liver nodules < 2.0 cm for the differentiation between hepatocellular carcinoma and regeneration nodules.…”
Section: Discussionmentioning
confidence: 99%
“…Caturelli showed that 69% of new nodules in a cirrhotic liver are malignant. 19 Moreover, liver cell dysplasia is found in 60% of cirrhotic livers containing hepatocellular carcinoma and in only 10% of non-cirrhotic livers.…”
Section: Discussionmentioning
confidence: 99%